2004
DOI: 10.1248/bpb.27.1965
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activity of 10 Different Plant Polyphenols against Bacteria Causing Food-Borne Disease

Abstract: Recently, many biochemical and epidemiologic studies have revealed that polyphenols of various foods and herbs are beneficial to human health, and some extracts of polyphenolrich plants, such as green tea and grape seed, have been applied to functional foods or supplements. The potent biological activities of green tea polyphenols in, for example, cancer and cardiovascular disease prevention, 1) have in particular been attracting scientists in medicinal and pharmaceutical fields. Tea polyphenols were also show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

29
294
13
11

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 421 publications
(347 citation statements)
references
References 19 publications
29
294
13
11
Order By: Relevance
“…Concerning the action of the compounds found in the extracts in bacterial cells, it is known that the flavonoids act in bacterial cells through the formation of complexes between proteins and the cell wall, causing its rupture (Taguri et al, 2004). On the other hand, tannins act in the microorganisms by preventing their growth through the inhibition of the transport of nutrients and the formation of complexes between the tannins and the bacterial cell wall (McSweeney et al, 2001).…”
Section: Resultsmentioning
confidence: 99%
“…Concerning the action of the compounds found in the extracts in bacterial cells, it is known that the flavonoids act in bacterial cells through the formation of complexes between proteins and the cell wall, causing its rupture (Taguri et al, 2004). On the other hand, tannins act in the microorganisms by preventing their growth through the inhibition of the transport of nutrients and the formation of complexes between the tannins and the bacterial cell wall (McSweeney et al, 2001).…”
Section: Resultsmentioning
confidence: 99%
“…Punicalagin exhibits multiple biological effects, including antioxidant, antiproliferative, antiviral, and antimicrobial activities (Taguri et al, 2004;Aqil et al, 2012;Yang et al, 2012;Xu et al, 2016). Moreover, it has shown anti-inflammatory properties both in vitro and in vivo (Jean-Gilles et al, 2013;Olajide et al, 2014;Xu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…It has long been known that polyphenols, such as flavonoid and epicatechin, are efficient scavengers of free radicals (Sichel et al, 1991). Plant polyphenols (PP) have also exhibited antimicrobial activity against bacteria that cause food-borne diseases (Taguri et al, 2004;Percival et al, 2006;Kim et al, 2009). Previous reports have shown that polyphenols from olive leaves exert great antimicrobial activity (Sudjana et al, 2009), tea polyphenols improve the balance of gut microflora in calves (Ishihara et al, 2001) and inhibit the proliferation of Chlamydia (Yamazaki et al, 2003), apple polyphenol extracts prevent damage to human gastric epithelial cells (Graziani et al, 2005), and polyphenols from grape seeds could prevent oxidative damage to cellular DNA in vitro (Fan and Lou, 2004).…”
Section: Introductionmentioning
confidence: 99%